Assistance For Early Detection Of 2-Minute Assessment in Narcotic Correctional Institution - Shella Febrita Puteri Utomo; Eli Lusiani; Nurul Latifah Sidiq (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
A correctional institution is a place to guide individuals who violate the law. Policies in correctional institutions include restrictions on the fulfillment of human rights, which all convicts experienced. This issue will almost certainly have an impact on his biological, social, and spiritual well-being. Health issues involving physical and psychological complaints are difficult to distinguish, making it difficult for nurses in correctional institutions to determine the appropriate treatment. Physical complaints that are experienced repeatedly without any improvement become a debate between physical and psychological issues. Due to time constraints and a limited number of assessors, nurses face difficulties in conducting assessments. Early detection is one of the initial assessment efforts to identify problems so that appropriate interventions can be chosen. Based on the problems listed above, an early detection assessment method using the 2-minute method can be used to help nurses quickly make a diagnosis and determine the best referral path